The impact of weather Condition Changes on Vertical Distribution of Sulfides in Lake Maninjau Based on Observation Data - Putri, Mutiara Rachmat; Jasalesmana, Taofik; Abdurrachman, Mirzam; Henny, Cynthia; Nomosatryo, Sulung; Albani, Alif Shidqie (BRIN Publishing, 2024)
Sulfide is a crucial parameter in volcanic lakes, as its levels and fluctuations in the lake determine the origin of sulfide and the extent of its impact on the lake ecosystem. In stratified lakes, the sulfide produced tends to be retained beneath the oxic layer. The sulfides rise towards the surface as the oxic layer thins triggered by decreased water column thermal stratification. Meanwhile, the strength or weakness of thermal stratification is greatly influenced by weather conditions. Lake Maninjau is a volcanic lake with a relatively high sulfide content. Its vertical distribution in the water column is highly dependent on the stratification of the water column. When stratification disappears, sulfide rises to the surface (locally known as tubo belerang) and has a negative impact on surface biota. The objective of this study is to examine the distribution of sulfides in the water column of Lake Maninjau under two different weather conditions. We perform two surveys to measure physicochemical parameters and sulfide concentration on 26‒29 November 2022 and 25‒26 August 2023 considering the seasonal pattern. We found that air temperatures and sunshine duration combined with precipitation and wind speed drive the thermal stratification of the water column. The lower air temperature, shorter sunshine duration, higher precipitation, and stronger wind speed in the first survey (west monsoon) compared with the second survey (east monsoon) resulted in lower stratification and triggered the elevated sulfide to the surface. In the middle of the lake, the surface sulfide measured during the first survey was 4.16 µg/L. Meanwhile, in the second survey, it was only observed at 1.16 µg/L. The distribution of sulfides within the water column of Lake Maninjau is regulated by the stratification of the water column, a process directly impacted by weather conditions.